Integrated Seven Tools Approach Reduces Flat Glass Defects: Integrasi Pendekatan Seven Tools Untuk Mengurangi Cacat Kaca Lembaran - Citra Wahyuning; Rr. Rochmoeljati (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Product quality control is a central requirement in manufacturing because defects can reduce production performance, increase waste, and weaken company reputation. Specific Background: PT XYZ, a major flat glass manufacturer in Indonesia, faced quality problems in flat glass production during January to September 2025, including inclusion, shellchip, scratch, and stain. Knowledge Gap: The manuscript identifies the need for structured defect analysis, causal diagnosis, and priority repair strategies to minimize flat glass product defects. Aims: This study aimed to identify flat glass defect types using Seven Tools and formulate quality improvement proposals using New Seven Tools. Results: The study recorded 567 defective units. Shellchip was the dominant defect, accounting for 50% or 285 units, followed by scratch at 22% or 123 units, inclusion at 16% or 91 units, and stain at 12% or 68 units. The proposed priority improvements were tightening raw material quality checks from suppliers, implementing double checks during press cutter machine setting, routinely cleaning dirt on the roll, conducting spray tests before coating, and creating a preventive maintenance schedule for coating machines. Novelty: The study combines Seven Tools for quantitative defect analysis with New Seven Tools for structured causal exploration and improvement prioritization. Implications: The findings offer practical quality control actions for reducing flat glass defects and strengthening production reliability. Highlights: A total of 567 faulty units were recorded from January to September 2025. Scratch, inclusion, and stain followed at 22%, 16%, and 12%. Five priority actions addressed supplier checks, cutter setup, roll cleaning, spraying, and maintenance. Keywords: Flat Glass, New Seven Tools, Product Defect, Seven Tools, Quality Control